Estratigrafia de sequências e proveniência sedimentar do Supergrupo Minas e Grupo Itacolomi no Quadrilátero Ferrífero, MG, Brasil - Gabriel Faria Gonçalves (2021)
The Minas-Itacolomi is a palaeoproterozoic meta-sedimentary megassequence in the Iron Quadrangle (Quadrilátero Ferrífero) metallogenic province in southeastern Brazil. It records a continental rift to passive margin to foreland basin transition. From the perspective of sequence stratigraphy, five sequences could be determined, providing information of the Palaeoproterozoic relative sea-level changes, summarized in the Minas-Itacolomi Basin stratigraphic chart. The main global event recorded in these meta-sedimentary units is the Great Oxidation Event. The interpretations were made possible through the systematic facies recognition (41 in total), followed by their associations, and the identification of depositional systems (9 repeating, in total), system tracts (also 9), and sequences (in that order). Caraça and Itabira Groups correspond to the first depositional sequence, where Lowstand, Transgressive, and Highstand System Tracts were identified. The Piracicaba Group hosts two Depositional Sequences and four system tracts. Sabará and Itacolomi Groups are the two top sequences, both related to a foreland basin development, where the underfilled and overfilled system tracts could be recognized. Sedimentary provenance for the stratigraphic units of Minas-Itacolomi Basin was mainly based on detrital zircon U-Pb age spectra of previous authors’ databases, and also based on palaeocurrent field data and thickness variations. All of the stratigraphic units of Minas-Itacolomi Basin share detrital zircons from Archaean sources, from both Rio das Velhas Supergroup and crystalline basement. Only Sabará and Itacolomi Groups presented bimodal U-Pb age histograms thus indicating Archaean and Palaeoproterozoic provenances. The later provenance is directly related to the tectonic inversion due to the Mineiro Belt in Southeastern Iron Quadrangle.